On the Issue of Future and Value of Empirical Sociology in Russia - Irina V. Popova (Социологическая наука и социальная практика, 2014)
The article raises such problems of the state of empirical sociology as professional qualification of the young generation of Russian sociologists, incompetent use of social study methods in related sciences, and public negative attitude of sociologists themselves towards quantitative sociology. The author proves that the stand of sociologists engaged in self-criticism is not corroborated by convincing arguments that would prove the ineffectiveness of the opinion poll method. The problem is that the researchers themselves fail to comply with the requirements of the sampling method and the development of tools. The article describes the author’s methods of longitudinal study performed by means of narrative interview and contains a personal autobiography written by the narrator (written tradition). The author shows what a deep access to the subjective world one can get with the help of a method characterized by its fully expressed subjectness. The methods developed by the author are remarkable because they leave no doubt that in this case the relations between the interviewer and the informant are interpersonal relations of two subjects of communication, which makes them dialogue relations, although the communication is carried out through a transcript. This has a considerable impact on the possibility of recording social processes, which is particularly important in the age of changes. The narrative message, consisting in describing one’s life journey as a history of relations between the individual and society in the form of an autobiography, has enabled the informant to arrange the reality of his life the way he sees it at this moment. The article contains a description of obtained results which deserves publication for enriching the theory of qualitative sociology on the one hand, and for better understanding of social reality on the other. The task of understanding social reality results from the processes going on within the society at the turn of a new era of its existence, and this is unique in itself.